Regional tourist heterogeneity in Spain: A dynamic spatial analysis - Almeida, Alejandro; Golpe, Antonio A.; Justo, Raquel (Elsevier Ltd, 2022)
Spain is one of the most visited countries in the world. However, given that the number of tourist arrivals hugely differ among Spanish regions, notable tourist regional inequalities are perceived in this country. In this context, spatial econometric techniques can be used as an instrument to understand these regional disparities. In particular, this work analyses the existence of regional spillovers in Spain, while also identifying the degree of sensitivity of the different regions to fluctuations in the general trends of the domestic and foreign tourist arrivals. Our results reveal (i) that the tourist arrivals are persistent over time, (ii) the presence of spatial dependence between regions in terms of domestic and international tourism —the latter being greater— and (iii) the existence of heterogeneity between regions in terms of sensitivity to tourist arrivals. These findings may favor the design of a common strategy to promote the alleviation of current regional inequalities as well as better tourism strategies to face tourism changes, either as general trends or unexpected events.
Keywords: heterogeneity; regional; Spain; spatial analysis; tourism; Scopus; JCR